2019
DOI: 10.2174/1874431101913010002
|View full text |Cite
|
Sign up to set email alerts
|

Primary Healthcare Data Management Practice and Associated Factors: The Case of Health Extension Workers in Northwest Ethiopia

Abstract: Background:Collecting quality and timely healthcare data is crucial to improve health service performance. Objective:This study aimed at assessing data management practice and associated factors among health extension workers in East Gojjam zone, Northwest Ethiopia. Materials and Methods:An institution based cross-sectional study was conducted in 2014 among 302 health extension workers. Data were collected using a selfadministered questionnaire and analyzed using SPSS version 20. The study objectives were desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…The included studies reported that the utilization of routine health information among health workers ranged from 32.9% [ 25 ] to 97.1% [ 9 ]. Five of the studies included in this review were conducted from Amhara region [ 9 , 21 , 26 28 ], two were from Southern Nations Nationalities and People’s Region (SNNPR) [ 29 , 30 ], two were from Oromia region [ 25 , 31 ], and the remaining one was from Dire Dawa administrative city [ 24 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The included studies reported that the utilization of routine health information among health workers ranged from 32.9% [ 25 ] to 97.1% [ 9 ]. Five of the studies included in this review were conducted from Amhara region [ 9 , 21 , 26 28 ], two were from Southern Nations Nationalities and People’s Region (SNNPR) [ 29 , 30 ], two were from Oromia region [ 25 , 31 ], and the remaining one was from Dire Dawa administrative city [ 24 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…This finding was somewhat comparable to the study in Northwest Ethiopia where 53.3% of health extension workers had good data management practice. 31 However, it was considerably higher than the HIS assessment conducted in Zanzibar and Jamaica whereas data management practice were 27%, and 48%, respectively. 26,27 This explanation might be due to the difference in the study setting and the variation in health information system structures between Ethiopia and those countries.…”
Section: Discussionmentioning
confidence: 83%
“…The questionnaire was adopted from WHO measure evaluation tools of Health Metrics Network (HMN), Performance of Routine Information Systems Management (PRISM) tools, and related studies. 2,7,31,32,36,43 A pretested self-administered questioners were filled by health professionals in order to assess health data management practice, socio-demographic, behavioral, technical, and organizational factors. The questioners consisted of 8 items for socio-demographic and 26 items for behavioral factors.…”
Section: Data Collection Tool and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations